THE COURT ON APPRECIATION. (The Accounting Review, 1930)
Abstract The article presents a ruling of a judge in the case of Bluefield Co. versus Pub. Serv. Comm on the issue of appreciation. A company since 1899 has owned and operated all the street railway lines in the City of Baltimore, Maryland. Its present capital structure consists of $24,000,000 of common stock, $38,000,000 of ordinary bonded indebtedness and $14,000,000 of perpetual income bonds. The present value of the property used was fixed by the Commission at $75,000,000. Included in this valuation is $5,000,000 for easements in the streets of Baltimore. The Commission fixed a rate of fare permitting the company to earn a return of 6.26 per cent on this valuation. Annual returns upon capital and enterprise, like wages of employees, cost of maintenance and related expenses, have materially increased the country over... what may be a fair return for one may be inadequate for another, depending upon circumstances, locality, and risk "The return should be reasonably sufficient to assure confidence in the financial soundness of the utility and should be adequate, under efficient and economical management to maintain and support its credit and enable it to raise the money necessary for the proper discharge of its public duties."